2004
DOI: 10.2320/matertrans.45.727
|View full text |Cite
|
Sign up to set email alerts
|

IMC Growth and Shear Strength of Sn-Ag-Bi-In/Au/Ni/Cu BGA Joints During Aging

Abstract: The growth kinetics of intermetallic compound (IMC) layers formed between Sn-3Ag-6Bi-2In ball-grid-array (BGA) solder and Au/Ni/ Cu substrate by solid-state isothermal aging were examined at temperatures between 343 and 443 K for 0 to 100 days. A quantitative analysis of the IMC layer thickness as a function of time and temperature was performed. The intermetallic layer exhibited a parabolic growth at the given temperature range. Because the values of the time exponent (n) are approximately 0.5, the layer grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 22 publications
3
53
0
Order By: Relevance
“…15(b). Similar results of accelerated growth at higher aging temperature can be found in previous reports, but without any discussion 3,10,16) except for Yoon et al 5) Figure 17 shows growth rates in several systems of high Sn and pure Ni, which were re-plotted from previous works. 10,16,17) Because these data show fairly good agreement, this result is essential.…”
Section: Growth Kinetics Of Imcsupporting
confidence: 74%
See 2 more Smart Citations
“…15(b). Similar results of accelerated growth at higher aging temperature can be found in previous reports, but without any discussion 3,10,16) except for Yoon et al 5) Figure 17 shows growth rates in several systems of high Sn and pure Ni, which were re-plotted from previous works. 10,16,17) Because these data show fairly good agreement, this result is essential.…”
Section: Growth Kinetics Of Imcsupporting
confidence: 74%
“…Neither Ag of Sn-3Ag-0.5Cu and Sn-3.5Ag solder nor Pb of Sn-37Pb solder was involved in interfacial reactions. In this study, EPMA quantitative analysis confirmed that IMC formed at the interface of the sample after long-term aging is (Ni,Cu) 3 Previous results showed that the IMCs formed at the interface of Sn-Ag-Cu solder and pure Ni depended on the Cu concentration in the solder material. Zeng et al 6) pointed out that the formation of (Cu,Ni) 6 Sn 5 dominated at the…”
Section: Morphology Of Imcsupporting
confidence: 50%
See 1 more Smart Citation
“…Therefore, the pursuit of Pb-free solder has become an important issue for electronic material research, and has led to extensive research and development work. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Many different solder alloys have been proposed as potential Pbfree solders and the most promising of these falls into the category of the Sn-Ag, Sn-Ag-Cu and Sn-Cu family of alloys. 13,14) Recently, compared with Sn-Ag solders, Sn-Zn solders have been highly recommended as a substitute for eutectic Sn-Pb solder due to their low melting point, excellent mechanical properties and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, IMCs such as Cu 6 Sn 5 and Cu 3 Sn easily grow at the interface between the copper interconnections and the lead-free solder bump. [3][4][5][6][7] Since both the mechanical and electrical properties of the IMC are quite different from those of tin and copper, the increase of the thickness of the IMC layer in the fine bump-interconnection joint structures may deteriorate the mechanical and electrical quality of the jointed structures.…”
Section: Introductionmentioning
confidence: 99%